Linking periodontitis and adverse pregnancy outcomes through CD14+ CD16+ monocytes. (August 2021) - Jagannathan, Raghunathan; Balaji, Thodur Madapusi; Varadarajan, Saranya; Bhuvaneswari, B.; Venkatakrishnan, C.J.; Lakshmi Priya, S.; Rajendran, Swaminathan; Sayed, Mohammed E.; Mugri, Maryam H.; Patil, Shankargouda
Abstract: One of the prevalent medical issues that deserve global attention is adverse pregnancy outcomes and preterm low birth weight deliveries which have a significant impact on neonatal health. Periodontitis has been implicated as a significant risk factor for adverse effects in pregnancy. Elevated levels of periodontal pathogenic bacteria and proinflammatory cytokines which are pathognomonic features of periodontitis are believed to cause placental infection and premature rupture of the amniotic membrane consequently leading to preterm delivery. The role of CD14+CD16+ monocytes as a causal link between periodontitis and adverse pregnancy outcomes has not been researched so far, although an elevation of these cells has been independently demonstrated in both conditions. With the available background information, this hypothesis attempts to derive a mechanistic link between periodontitis and adverse pregnancy outcomes through the participation of CD14+CD16+ monocytes.